PENGARUH AUDIT EXPERIENCE, PENGETAHUAN MENDETEKSI KECURANGAN DAN PROFESSIONALISME AUDITOR TERHADAP PERTIMBANGAN TINGKAT MATERIALITAS : Pada Kantor Akuntan Publik - Dara Elzha Santoso (2021)
The research was purpose to analyze the effect of audit experience, knowledge of detecting fraud's and professionalisme auditor's. The sample employ of this study is amounted to 81 respondens auditor's working profession at the Public Accountant Office in DKI Jakarta registered in the IAPI Directory with random sampling the methods. Data source use primary data. Data Collection method's are using questionnaires directly submitted to the Public Accounting Office in DKI Jakkarta. Data analyze used technique Smart PLS 3.3.3 with a significance level of 5%. The results of this study indicated that was (1) Audit Experience has a significant effect positive in Determinant of Materiality Level (2) Knowledge Of Detecting Fraud's has a significant effect positive on Determinant of Materiality Level (3) Professionalisme Auditor's has a significant effect positive on Determinant of Materiality Level.